Clinical findings and risk factors associated with oral cancer: a prospective study - Gupta, Yashna; Singh, Parvinder; Bedi, Neeru; Garg, Pardeep; Singh Banipal, Raja Paramjit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Oral cancer is associated with high morbidity and mortality and therefore it represents a grave health problem worldwide. However there is scarcity of the studies in the literature regarding the prognostic factors amongst the subjects. The aim of the present study is to determine the various risk factors and the most commonly affected sites by the oral squamous cell carcinoma amongst subjects of different age groups. Methods: The present prospective comparative study was conducted at the Department of Radiotherapy at Guru Gobind Singh Medical College and Hospital during a period of three months i.e. from April 2016 to June 2016. Patients were evaluated every week for a period of approximately 2 weeks. Examination of the oral cavity was done using probe and mouth mirror by trained personnel. TNM classification was used to classify tumour. Patient’s habits like alcohol and tobacco intake were also recorded. Complete demographic information was obtained from all the patients. All the data thus obtained was arranged in a tabulated form and analysed using SPSS software. Results: The study included a total of 60 subjects. There were 11 females in the study and 49 males in the study. There were 18.3% (n=11) subjects having cancer of tongue. There were 23.3% (n=14) subjects having cancer of buccal mucosa. Alveolar ridge carcinoma was seen in 8.3% (n=5) subjects. There were 22 patients (30%) having stage III carcinoma. Majority of the subjects i.e. 70% (n= 38) were at stage IV A according to TNM classification. Conclusions: From the above study we can conclude that there is lack of awareness amongst the people about oral cancer. They mostly present during advanced stage of the disease. Most of the subjects are males, showing there predisposition towards harmful habits.